2020
DOI: 10.1103/physrevresearch.2.013009
|View full text |Cite
|
Sign up to set email alerts
|

Inertial bifurcation of the equilibrium position of a neutrally-buoyant circular cylinder in shear flow between parallel walls

Abstract: The motion of a neutrally buoyant, rigid circular cylinder in simple shear flow of a Newtonian fluid between parallel walls is calculated for various particle Reynolds numbers, Re p = Ga 2 /ν, via the lattice Boltzmann method. Here, G is the velocity gradient of the ambient shear, a is the radius of the particle cross section, and ν is the kinematic viscosity of the fluid. An inertial lift force perpendicular to the ambient shear has a single zero crossing at the center of the channel below a critical Re p , c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
(52 reference statements)
4
16
0
Order By: Relevance
“…As demonstrated by Asmolov (1999), a neutrally buoyant sphere in shear flow bounded by a single wall experiences no equilibrium position, as the lift force is always directed away from the wall. We previously showed that the equilibrium position of a circular cylinder in confined shear flow experienced a similar inertial bifurcation as a result of the second confining wall (Fox et al 2020). Our present findings indicate that this phenomenon persists in three-dimensional confined shear flows.…”
Section: Lift Force On a Transversely Fixed Spheresupporting
confidence: 78%
See 2 more Smart Citations
“…As demonstrated by Asmolov (1999), a neutrally buoyant sphere in shear flow bounded by a single wall experiences no equilibrium position, as the lift force is always directed away from the wall. We previously showed that the equilibrium position of a circular cylinder in confined shear flow experienced a similar inertial bifurcation as a result of the second confining wall (Fox et al 2020). Our present findings indicate that this phenomenon persists in three-dimensional confined shear flows.…”
Section: Lift Force On a Transversely Fixed Spheresupporting
confidence: 78%
“…We previously showed that the equilibrium position of a circular cylinder in confined shear flow experienced a similar inertial bifurcation as a result of the second confining wall (Fox et al. 2020). Our present findings indicate that this phenomenon persists in three-dimensional confined shear flows.…”
Section: Neutrally Buoyant Sphere In Confined Shear Flowmentioning
confidence: 89%
See 1 more Smart Citation
“…Over the past 50 years, not less than 20 experimental, analytical and computational studies have been devoted to the WLF, see works [111,112] and references therein. We also could not resist the temptation to measure this effect in our system.…”
Section: Discussionmentioning
confidence: 99%
“…We chose WLF as a benchmark to check the accuracy of the LB algorithm in our simulations. Therefore, the obtained results were compared with two recent computational studies: one for low translational Reynolds numbers [111] Re γ = {0.1, 0.01} and other one for intermediate-low [112] -Re γ = {1, 3, 10};…”
Section: Discussionmentioning
confidence: 99%